The effect of thromboembolic prophylaxis after cesarean section in patients with hypertensive disorders - SOYSAL, SUAH (My University, 2023)
OBJECTIVE: This study aims to compare the effect of thromboembolic prophylaxis in patients diagnosed with hypertensive disorders of pregnancy undergoing cesarean section. METHODS: Three hundred and eighty-six patients were included in the study. The patients were divided into groups according to the type of hypertensive disorders of pregnancy and whether thromboembolism prophylaxis was applied or not. The thromboembolic event incidence and other pregnancy outcomes were compared. RESULTS: Nonadministration of thromboprophylaxis was recorded in 210 patients. Eleven patients had thromboembolic events (5%). Among 176 patients who received thromboprophylaxis, only two patients (1%) had a thromboembolic event (p<0.05). CONCLUSION: There is an increased tendency to thromboembolism in pregnancy. The incidence increases in the presence of hypertension accompanying pregnancy. In our study, the importance of thromboembolism prophylaxis on peri-postnatal complications in patients with hypertensive disorders of pregnancy was emphasized.
Keywords: Anticoagulants; hypertensive disorders of pregnancy; prophylaxis; thromboembolism